Ketoacidosis as unexpected adverse reaction SGLT2 inhibitor - T. M. Bukatina; A. S. Kazakov; N. Yu. Velts; M. A. Darmostukova; K. E. Zatolochina; R. N. Alyautdin; V. P. Dobrynin; B. K. Romanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Inhibitors of the sodium-glucose cotransporter-2 SGLT2 is a new class of hypoglycemic drugs. This article presents the information on FDA reports (2013-2015) and AIS (May 2015 - February 2016) on the risk of new adverse reaction - ketoacidosis. Conjectural pathophysiological mechanisms of ADR associated with this class of drugs, which could lead to its development are presented.